Analisis Risiko Kredit Bermasalah Dalam Perspektif Akuntansi Keuangan Pada KSP CU Bahtera Sejahtera Tempat Pelayanan Nita - Todang, Mauretshia Putri; Niken Aurelia, Pipiet; Maria Dilliana, Siktania (Jurnal Projemen UNIPA, 2026)
This study aims to analyze the risk of non-performing loans from a financial accounting perspective at the Bahtera Sejahtera Credit Union where Nita works. This study was conducted at the Bahtera Sejahtera Credit Union where Nita works from August 1 to December 19, 2025, located in Nita Village, Nita District, Sikka Regency. Data was collected using interviews, observation, documentation, and literature study techniques. Data analysis techniques consisted of three steps, namely data reduction, data presentation, and conclusion drawing and verification. The results of this study indicate that non-performing credit risk is one of the main risks faced by KSP CU Bahtera Sejahtera Tempat Pelayanan Nita and has a significant effect on the cooperative's financial condition. This risk mainly arises due to delays and the inability of members to fulfill their loan payment obligations in accordance with the agreed terms. From a financial accounting perspective, non-performing credit risk management has been carried out through a measurement process based on loan collectability, recognition by forming a credit loss reserve, and presentation and disclosure as reflected in the financial statements and notes to the financial statements. The application of these accounting treatments aims to present financial information that is fair, transparent, and reliable to both internal and external parties of the cooperative. Non-performing credit risk has a direct impact on the decline in surplus (SHU) and has the potential to disrupt the liquidity of the cooperative. Therefore, credit risk control through loan feasibility analysis, payment monitoring, and the establishment of adequate loss reserves is essential to maintain the stability and sustainability of the cooperative's business. Thus, the application of appropriate financial accounting in managing credit risk is an important factor for KSP CU Bahtera Sejahtera Tempat Pelayanan Nita in improving financial performance and maintaining member trust.